Strigolactone versus gibberellin signaling: reemerging concepts? - Wallner, Eva-Sophie; López-Salmerón, Vadir; Greb, Thomas (Planta, 2016)
In this review, we compare knowledge about the recently discovered strigolactone signaling pathway and the well established gibberellin signaling pathway to identify gaps of knowledge and putative research directions in strigolactone biology
Gesehen am 17.02.2017